“Milking” the Consumer? Consumer dissatisfaction and regulatory intervention in the Ontario milk industry during the Great Depression - Ebejer, Andrew (Ontario History, 2010)
In the early 1930s, Ontario’s milk industry was crippled by a series of “price wars” that undermined the profit-making ability of both milk producers and distributors. The province responded to this untenable situation by creating the Ontario Milk Control Board (MCB), which eventually stabilized the industry through licensing, bonding, and fixed price agreements. Congruent to this stabilization was the gradual inflation of consumer milk prices—much to the angst of a consuming public that found it difficult to subsist. Communists and housewives alike protested in Ontario cities. Alternative, sometimes radical, solutions were proposed. Consumer advocates additionally sought a pure and nutritious product for their undernourished children. Debates over pasteurization, in particular, raged alongside boycotts over cost. Yet, this emerging consumer movement attracted little government support and enjoyed only marginal success. Producers and dairies successfully mobilized the MCB on their behalf, whereas consumers failed to achieve price concessions and were often constrained by the state.